2020
DOI: 10.1007/s40200-020-00576-3
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and silymarin: a fight against liver damage in NAFLD associated - prediabetic disease

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is common in both prediabetic patients and healthy overweight individuals, yet it remains understudied. This study investigates the effects of hepatic steatosis on fibrosis and evaluates the major predictors of liver injury in prediabetes and whether this damage is reversible with Mediterranean diet and administration of the nutraceutical silymarin. Methods First, a case-control study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…In their study, Colletta et al assessed the effect of silymarin on prediabetic patients. The findings of this study only showed the positive impact of silymarin on HbA1c (Colletta et al, 2020). However, it was the only study arm that examined silymarin in our review.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In their study, Colletta et al assessed the effect of silymarin on prediabetic patients. The findings of this study only showed the positive impact of silymarin on HbA1c (Colletta et al, 2020). However, it was the only study arm that examined silymarin in our review.…”
Section: Discussionmentioning
confidence: 65%
“…The main finding of this review is that from 31 arms, 21 arms had positive effects on at least one glycemic indices or one of the other cardiometabolic factors (Cicero et al, 2020; Colletta et al, 2020; Derosa, D'angelo, et al, 2020; Derosa, Maffioli, et al, 2020; Karandish et al, 2021; Karandish et al, 2022; Ming et al, 2021; Ribeiro et al, 2019; Thota et al, 2019; Thota et al, 2020; Wang et al, 2020; Yang et al, 2017; Yang, Liu, et al, 2020; Yari et al, 2021; Zhang et al, 2018). However, 10 arms had no effective results on any of the measured factors (Funamoto et al, 2019; Moreno‐Ulloa et al, 2018; Pollack et al, 2017; Shanobin et al, 2007; Yang et al, 2021; Yang, Ling, et al, 2020; Ye et al, 2021, 2015).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Silymarin has the potential to regress NAFLD in patients under the Mediterranean diet than in the Mediterranean diet alone group. For instance, along with the Mediterranean diet, twice-daily administration of silymarin (210 mg) for 6 months has led to significant improvement in the glycemic profile and regression of liver damage (Colletta et al, [ 111 ]). Silymarin, vitamin C, vitamin E, and coenzyme Q10 and selenomethionine (Medronys epato®) contain a capsule twice a day for 45- and 90-days treatments that has histologically improved liver function and reduced the marker enzymes of liver toxicity (ALT, AST, ALP, and GGT) and lipid markers (total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and TG) in serum of NAFLD patients (Curcio et al, [ 112 ]).…”
Section: Antioxidants Used In Clinical Trial For Nafldmentioning
confidence: 99%
“…It is commonly used in the treatment of simple or alcoholic fatty liver acute and chronic hepatitis, and other diseases with abnormal liver function (11)(12)(13). However, the standard methods for the determination of SCN, SDN, SBA, SBB, ISBA, and ISBB in SMS have not been established in China.…”
Section: Introductionmentioning
confidence: 99%